2022
DOI: 10.3390/ijms232012516
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry Component Kuwanon C Exerts Potent Therapeutic Efficacy In Vitro against COVID-19 by Blocking the SARS-CoV-2 Spike S1 RBD:ACE2 Receptor Interaction

Abstract: There has been an immense effort by global pharmaceutical companies to develop anti-COVID-19 drugs, including small molecule-based RNA replication inhibitors via drug repositioning and antibody-based spike protein blockers related to cell entry by SARS-CoV-2. However, several limitations to their clinical use have emerged in addition to a lack of progress in the development of small molecule-based cell entry inhibitors from natural products. In this study, we tested the effectiveness of kuwanon C (KC), which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…We discovered that CBNA interacted with Tyr449 and Gln498, producing three conventional H and three pi-alkyl bonds with Tyr453, Tyr495 and Tyr505, and one Alkyl bond with Arg403, respectively ( Figure 1 B). Similarly, Kuwanon C (KC) was identified that could interact with Gln498 of spike S1 RBD [ 45 ]. CBGVA formed two conventional H bonds with Gly496 and Asn501, as well as four pi-alkyl bonds with Tyr453, Tyr495, and Tyr505, which was identical to the KC interaction with ACE2 [ 45 ], and one Pi-Pi bond with Tyr505 ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We discovered that CBNA interacted with Tyr449 and Gln498, producing three conventional H and three pi-alkyl bonds with Tyr453, Tyr495 and Tyr505, and one Alkyl bond with Arg403, respectively ( Figure 1 B). Similarly, Kuwanon C (KC) was identified that could interact with Gln498 of spike S1 RBD [ 45 ]. CBGVA formed two conventional H bonds with Gly496 and Asn501, as well as four pi-alkyl bonds with Tyr453, Tyr495, and Tyr505, which was identical to the KC interaction with ACE2 [ 45 ], and one Pi-Pi bond with Tyr505 ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Kuwanon C (KC) was identified that could interact with Gln498 of spike S1 RBD [ 45 ]. CBGVA formed two conventional H bonds with Gly496 and Asn501, as well as four pi-alkyl bonds with Tyr453, Tyr495, and Tyr505, which was identical to the KC interaction with ACE2 [ 45 ], and one Pi-Pi bond with Tyr505 ( Figure 1 C). The previous study showed that CBD and CBN formed two and one H bonds, respectively, at the Glu166 and Met165 sites [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the half-life of soluble ACE2 is very low, which means that it requires multiple administrations and makes treatment difficult and cumbersome. The latter two considerations may also apply for other low molecular weight compounds [ 123 , 124 ]. Alternatively, one may therefore consider topical administration or approaches blocking cell-bound ACE2 with compounds to prevent RBD–ACE2 interaction.…”
Section: Molecular Interaction Assays Miasmentioning
confidence: 99%
“…In vitro studies showed that this natural compound inhibited the SARS-CoV-2 infection by interacting with both the viral spike proteins and the host ACE2 receptor cells with an IC 50 value of 91.4 μM at a concentration range of 25 μM to 100 μM. Furthermore, in silico studies demonstrated the more stable binding interactions of ligands with spike proteins compared to ACE2 receptors [ 53 ]. Some naturally occurring flavonoids (myricetin, quercetin, kaempferol, flavanone, and licoflavone C) were found to inhibit the enzymatic activities of SARS-CoV-2 by selectively antagonizing the action of NSP13 at nanomolar and micromolar concentrations.…”
Section: In Vitro and In Silico Studiesmentioning
confidence: 99%